تكامل التصميم المعماري مع الخلايا الشمسية في المباني - ودح, هاني; شحود, رؤى (Latakia University Journal -Engineering Sciences Series, 2018)
When the world began discussing the issues of climate change resulting from the use of fossil fuels, the use of solar energy emerged in different forms. The current buildings are responsible for the use of larger quantities of energy for lighting and heating, cooling and miscellaneous equipment powered by fossil fuels. For example in Syria residential buildings consume about 43% of energy consumed in Syria for operating purposes. From this, governments and societies should have high will to replace fossil fuels with solar energy, that is free and available everywhere. The main problem is that the parameters imposed by using solar technologies may lead to flaws in the whole architectural system of the building design, and unless they are manufactured and adjusted their determinants modified to become an architect instrumental in the General form service, in addition to their important role in energy production, the consumer attraction will remain limited, and the architect will remain unable to integrate them as a positive element in the design to improve technical and functional level. Thus the main objective of the research is to create an architectural integration between elements of clean energy and architectural solutions for buildings. عندما بدأ العالم مناقشة قضايا التغير المناخي الناجمة عن استخدام الوقود الأحفوري، ظهر استخدام الطاقة الشمسية بأشكال مختلفة. وتعتبر المباني الحالية مسؤولة عن استخدام الكميات الأكبر من الطاقة للإنارة والتدفئة، والتبريد واستخدام المعدات المتنوعة التي تعمل بالطاقة الأحفورية غالباً. فعلى سبيل المثال في سوريا تستهلك المباني السكنية لأغراض التشغيل 43% من الطاقة المستهلكة في سوريا. وعليه لا بد أن تكون الارادة عالية عند الحكومات والمجتمعات لاستبدال الوقود الأحفوري بالطاقة الشمسية المجانية والمتوافرة في كل مكان. ان المشكلة الرئيسية تكمن بأن المحددات التي يفرضها استخدام التقنيات الشمسية قد تؤدي الى خلل في تكامل المنظومة المعمارية الكلية لتصميم المبنى، وعليه إذا لم يتم تصنيعها وتعديلها وضبط محدداتها لتصبح عنصراً معمارياً فعالاً في خدمة الشكل العام بالاضافة الى دورها المهم في انتاج الطاقة.فان استقطابها للمستهلك سيبقى محدوداً وسيبقى المعماري عاجزاً عن إدخالها كعنصر من العناصر الإيجابية في التصميم. وبالتالي ان الهدف الأساسي للبحث هو خلق تكامل معماري بين عناصر الطاقة النظيفة والحلول المعمارية للمباني.